Developing Local Creativity in Songa Village by Utilizing Natural Products Around the Environment - Yustina Selong; Wanda Giovani; Yumita Yumita; Iren Iren; Eksel Jepon (STKIP Singkawang, 2022)
Community service is one of the main duties of a lecturer. The activity with the theme